Factores asociados a dolor crónico en pacientes sometidas a cesárea, atendidas en el Hospital Iquitos "César Garayar García", 2021 - Murayari Perez, Eloy Charles (Universidad Nacional de la Amazonía Peruana, 2022)
Chronic pain is one of the most frequent and important post-surgical complications, little is known about the mechanisms underlying the development of this pain and there is no consensus on the prevalence rates in the different forms of surgery, including cesarean section. This research project presents as a formulation of the problem: What are the factors associated with chronic pain in patients undergoing cesarean section treated at the Iquitos "Cesar Garayar Garcia" Hospital, 2021? general objective: To relate the factors associated with chronic pain in patients undergoing cesarean section treated at the Iquitos "Cesar Garayar Garcia" Hospital, 2021. Methodology: The Observational-analytical method will be used. Because the relationship between risk factors (preoperative factors, intraoperative factors and postoperative factors) and chronic pain (dependent variable) presented by patients undergoing cesarean sections attended at Cesar Garayar Garcia Hospital will be established. Longitudinal. Data will be collected at two times (3 and 6 months after the surgical procedure). The population will be made up of patients undergoing cesarean section during the year 2021 in the Obstetrics and Gynecology service of the Iquitos Hospital. The Sample According to the registry of the operating room of the Iquitos Hospital, approximately 150 caesarean sections are performed in a month.

El dolor crónico siendo una de las complicaciones posquirúrgicas más frecuentes e importantes, se sabe poco sobre los mecanismos subyacentes al desarrollo de este dolor y no existe consenso sobre las tasas de prevalencia en las diferentes formas de cirugía, incluida la cesárea. El presente proyecto de investigación presenta como problema: ¿Cuáles son los factores asociados al dolor crónico en pacientes sometidas a cesárea atendidas en el Hospital Iquitos “Cesar Garayar García” 2021? Objetivo general: Relacionar los factores asociados al dolor crónico en pa-cientes sometidas a cesárea atendidas en el Hospital Iquitos “Cesar Garayar García”, 2021. Metodología: se empleará el método Observacional-analítico. Porque se establecerá la relación entre factores de riesgo (factores preoperatorios, fac-tores intraoperatorios y factores postoperatorios) y el dolor crónico (variable dependiente) presentado las pacientes sometidas a cesáreas atendidas en el Hospital cesar Garayar García. Longitudinal. Se recolectarán los datos en dos momentos distintos (a los tres y a los seis meses de realizado el proce-dimiento quirúrgico). La población estará conformada por las pacientes sometidas a cesárea du-rante el año 2021 en el servicio de Gineco-Obstetricia del Hospital Iquitos. La Muestra Según el registro de sala de operaciones del Hospital Iquitos, en un mes se realizan aproximadamente 150 cesáreas.
Keywords: Dolor agudo; Cesárea; Dolor postoperatorio; Pacientes; https://purl.org/pe-repo/ocde/ford#3.02.02